Validity of weight estimation models in pigs reared under different management conditions - Sungirai, Marvelous; Masaka, Lawrence; Benhura, Tonderai Maxwell (Hindawi Publishing Corporation, 2015)
A study was carried out to determine the relationship between linear body measurements and live weight in Landrace and Large White pigs reared under different management conditions in Zimbabwe. Data was collected for body length, heart girth, and live weight in 358 pigs reared under intensive commercial conditions. The stepwise multiple linear regression method was done to develop a model using a random selection of 202 records of pigs.The model showed that age, body length, and heart girth were useful predictors of live weight in these pigs with significantly high positive correlations observed.The model was internally validated using records of the remaining 156 pigs and there was a significantly high positive correlation between the actual and predicted weights. The model was then externally validated using 40 market age pigs reared under communal conditions and there was a significantly low positive correlation between the actual and predicted weights. The results of the study show that while linear measurements can be useful in predicting pig weights the appropriateness of the model is also influenced by the management of the pigs. Models can only be applicable to pigs reared under similar conditions of management.